2016
DOI: 10.1111/nph.14158
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between mtDNA complexity and mtDNA replication mode in developing cotyledon mitochondria during mung bean seed germination

Abstract: The currently accepted model of recombination-dependent replication (RDR) in plant mitochondrial DNA (mtDNA) does not clearly explain how RDR progresses and how highly complex mtDNA develops. This study aimed to investigate the correlation between RDR and mtDNA complexity during mitochondrial development in mung bean (Vigna radiata) seed, and the initiation and processing of RDR in plant mitochondria. Flow cytometry, pulsed-field gel electrophoresis, electron microscopy, real-time PCR and biochemical studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 38 publications
(104 reference statements)
0
41
1
Order By: Relevance
“…Similar changes in mitochondrial DNA structures have been observed in the growth cycles (but not cell cycles) of cultured tobacco cells in pioneering studies by Oldenburg and Bendich (1996; for review, see Oldenburg and Bendich, 2015) and Chenopodium album cells (Backert and Börner, 2000). Rapid amplification of organellar DNAs has been observed around meristems Fujie et al, 1994) and at specific stages, such as during germination (Cheng et al, 2017) and at the start of cell culture (Satoh et al, 1993). The rapid amplification of organellar DNA independent of the host cell cycle also seems to be like that in phages that use RDR for DNA synthesis.…”
Section: Maintenance Of Mitochondrial Dna With Dynamic Mitochondriamentioning
confidence: 55%
See 2 more Smart Citations
“…Similar changes in mitochondrial DNA structures have been observed in the growth cycles (but not cell cycles) of cultured tobacco cells in pioneering studies by Oldenburg and Bendich (1996; for review, see Oldenburg and Bendich, 2015) and Chenopodium album cells (Backert and Börner, 2000). Rapid amplification of organellar DNAs has been observed around meristems Fujie et al, 1994) and at specific stages, such as during germination (Cheng et al, 2017) and at the start of cell culture (Satoh et al, 1993). The rapid amplification of organellar DNA independent of the host cell cycle also seems to be like that in phages that use RDR for DNA synthesis.…”
Section: Maintenance Of Mitochondrial Dna With Dynamic Mitochondriamentioning
confidence: 55%
“…If they do not exist, replication might occur only by RDR. Cheng et al (2017) recently observed the physical structures of DNA molecules isolated from mitochondria during the early germination of mung bean (Vigna radiata) seeds. At first, the DNA was in the form of simple linear molecules with sizes shorter than the genome size.…”
Section: Maintenance Of Mitochondrial Dna With Dynamic Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that this protein is involved in mismatch recognition , however a formal biochemical demonstration of this protein in mismatch repair or DNA processing has not been addressed to date. An alternative mechanism to explain the low mutation rates in plant organellar DNA, is the premise that organellar DNA replication is based on a recombination‐dependent replication mechanism . In this mechanism, double‐strand breaks generate regions of long homologies that are used for homologous recombination with one of the multiple copies of mitochondrial or plastid DNA as a template .…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms that mediate DNA replication in plant organelles are largely unknown. Several mechanisms like D‐loop, theta‐like, rolling circle, and recombination‐dependent DNA replication are proposed to account for DNA replication in mitochondrial and chloroplast genomes . Animal and plant mitochondrial genomes code for approximately the same number of essential genes.…”
Section: Introductionmentioning
confidence: 99%